Membrane behavior and coupled solute transport through a geosynthetic clay liner - Malusis, Michael Adam, author; Shackelford, Charles D., advisor; Olsen, Harold W., committee member; Nelson, John D., committee member; Ladanyi, Branka, committee member (Colorado State University. Libraries, 2001)
The ability of a geosynthetic clay liner (GCL) to act as a semi-permeable membrane that restricts migration of solutes, and the influence of this membrane behavior on solute transport through a GCL, are evaluated in this research. A coupled solute transport model that accounts for membrane behavior (i.e., salt-sieving, chemico-osmotic counter flow) in clay soils is developed. In addition, laboratory chemico-osmotic/ diffusion and column tests are conducted on specimens of a GCL subjected to potassium chloride (KCl) solutions. Measured chemico-osmotic efficiency coefficients (co) range from 0.14 to 0.63, and effective salt-diffusion coefficients (D*s) range from 2.38 x 10-10 m2/s to 7.83 x 10-11 m2/s for 10-mm-thick GCL specimens subjected to KCl source concentrations ranging from 0.0039 M to 0.047 M. The results indicate that two coupling effects limit KCl diffusion through the GCL: (1) an explicit coupling effect due to salt-sieving, as predicted by the coupled flux transport theory; and (2) implicit coupling characterized by a concentration-dependent decrease in D*s that ts related to the apparent tortuosity factor (τa). These effects are correlated with measured ω values for the GCL. Comparison of experimental results from column tests with model simulations based on independently measured values of ω and D*s (or τa) indicate that implicit coupling is more significant than explicit coupling for reducing solute flux through the GCL under diffusion-dominated conditions. The results of theoretical simulations indicate that lower values of solute flux and longer solute transit times through a soil membrane are predicted by coupled solute transport theory relative to advective-dispersive theory that neglects chemico-osmotic efficiency. The coupled transport model also provides better agreement with measured data from the column tests than advective-dispersive theory. Use of advective-dispersive theory to simulate solute transport through GCLs appears reasonable under diffusion-dominated conditions, provided that implicit coupling is included by using an appropriate value of D*s (or τa) that corresponds to the solute concentration.
Keywords: civil engineering; environmental engineering; geotechnology